Immunomodulatory mechanisms of action of calcitriol in psoriasis - Suravi Raychaudhuri; Anupam Mitra; Ananya Datta-Mitra (Wolters Kluwer Medknow Publications, 2014)
Background: Calcitriol is well known for its therapeutic efficacy in psoriasis, but its mechanism of action is still unclear. In this study, we tried to elucidate the precise mechanism of calcitriol for its therapeutic efficacy in psoriasis. Materials and Methods: Proliferation and apoptosis studies were done to determine the effect of calcitriol on normal human epidermal keratinocytes (NHEKs) and T lymphocytes. To elucidate the effect of Calcitriol on relevant chemokines and epidermal proteins of psoriasis, real-time polymerase chain reaction were done on the modified reconstructed human epidermis (RHE) an in vitro model of psoriasis. All experiments were done in triplicate. Results were expressed as mean ± standard error of mean. Results and Conclusions: In vitro, Calcitriol showed significant inhibition of NHEKs and T lymphocyte proliferation by inducing apoptosis of these cells. Moreover, in an in vitro model of psoriasis (RHE), Calcitriol significantly inhibited relevant gene expression of chemokines (Interleukin-8, Regulated upon Activation Normal T-cell Expressed and Secreted [RANTES]) and psoriasin (S100A7). Here, we observed that Calcitriol inhibits critical pathological events associated with the inflammatory-proliferative cascades of psoriasis. Calcitriol induced apoptosis of NHEKs and T lymphocytes as well as inhibited gene expression of relevant chemokines and epidermal proteins in the in vitro model of psoriasis.